Fully printed all-polymer tattoo/textile electronics for electromyography. (14th September 2018) - Bihar, Eloïse; Roberts, Timothée; Zhang, Yi; Ismailova, Esma; Hervé, Thierry; Malliaras, George G; De Graaf, Jozina B; Inal, Sahika; Saadaoui, Mohamed
Abstract: Driven by the ever-growing need for developing low-cost, easy-to-use, noninvasive diagnostic tools, biomedical devices that can be integrated on human skin or textiles have begun to emerge. These 'wearable' devices should couple electronics directly to the human skin and detect a variety of biologically relevant signals such as neuromuscular activity. In this work, we develop a simple, low-cost and customizable device to perform electromyography measurements based on electronics fabricated on tattoo paper. The electrodes are based on the conducting polymer poly(3, 4-ethylenedioxythiophene) doped with polystyrene sulfonate (PEDOT:PSS) and inkjet-printed on the conformable tattoo paper. Addressing the integration challenge common to such flexible electronic devices, we connect the tattoo electrodes to the acquisition system through a textile in the form of a wristband comprising printed PEDOT:PSS contacts. While the textile wristband conforms around the 'tattooed' skin, it enables a reliable contact with the electrodes beneath. We show that this tattoo/textile electronics platform is able to monitor the biceps activity of the arm during muscle contractions lasting for a period of 7 h, with comparable performance to conventional biopotential electrodes and without the use of gels or expensive metallic materials. Combining the tattoo electronics with the electronic textile improves the communication of skin-like electrodes with external electronics, renders a reliable and versatile system for detecting biopotential signals critical for myoelectric prosthesis, muscle injury prevention and/or detection.